Pengembangan Multimedia Interaktif DIAKSY (Digital Akuntansi Syariah) Berbasis Google Sites Pada Mata Pelajaran Akuntansi Perbankan Syariah - Triani, Widy (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2024)
This research was carried out with the aim of developing learning media in the form of interactive multimedia based on Google Sites in Islamic banking accounting subjects for class XII and to determine the feasibility of the media made. This interactive multimedia is called DIAKSY (Digital Islamic Accounting). In this study using the ADDIE development model, including analysis, design, development, implementation, and evaluation. Product trial activities were carried out by 20 students at SMK Negeri 2 Kota Mojokerto Class XII, Islamic Banking Department. Based on expert validation, the criteria are very feasible with an average percentage of eligibility for material experts of 88%, and the percentage of eligibility for media experts is 94.74%. As for the responses of the students, it was obtained that the criteria were very good at a percentage of 98%. Thus, the final result is that Google Sites-based interactive multimedia DIAKSY (Digital Accounting Sharia) products are very suitable to be used as learning media in the learning process with an average feasibility of ≥ 61%.